Forecasting Macedonian business cycle turning points using Qual VAR model - Magdalena Petrovska; Aneta Krstevska; Nikola Naumovski (National Bank of the Republic of Macedonia, 2016)
This paper aims to assess the usefulness of leading indicators in business cycle research and forecast. Initially we test the predictive power of the ESI within a static probit model as a leading indicator, commonly perceived to be able to provide a reliable summary of the current economic conditions. We further proceed by analyzing how well an extended set of indicators performs in forecasting turning points of the Macedonian business cycle by employing the Qual VAR approach of Dueker (2005). In continuation, we evaluate the quality of the selected indicators in pseudo-out-of-sample context. The results show that the use of survey-based indicators as a complement to macroeconomic data work satisfactory well in capturing the business cycle developments in Macedonia.
Keywords: F42; C25; C22; 330; Forecasting; Business cycle turning points; Qual VAR; MCMC; Latent variable